Comparison of asphaltene structure and morphology under different deasphaltene methods. (4th March 2017) - Kananpanah, S.; Kheirkhah, R.; Bayat, M.; Sadi, M.; Moosavian, M. Ali
ABSTRACT: Problems associated with asphaltene deposition during the production, transportation, and processing of crude oils are some of the important issues in oil industry. Thus, accurate identification of structure and surface morphology of asphaltene should be investigated. In this study, asphaltene are isolated from an Iranian heavy crude oil under three different experimental conditions by using heat (thermal deasphaltene), heat and toluene (thermal-toluene deasphaltene), and n-heptane (n-heptane deasphaltene) as precipitation agent. The effect of isolation method on the crystallite structure and surface morphology of asphaltene is characterized by X-ray diffraction and scanning electron microscope technique, respectively. It is found that extraction procedure has a strong influence on the physicochemical properties of the isolated asphaltene. The results showed that at thermal deasphaltene solid such as micellar the shape was the dominant morphology of asphaltene particles that cause the least height of the crystallites and number of aromatic sheets in a stacked cluster. This morphology changes to semisolid smooth surface and agglomerated asphaltene with cavities by altering the separation method to thermal-toluene deasphaltene and n-heptane deasphaltene. The maximum heights of the crystallites belong to n-heptane deasphaltene.